(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2022)
Objectives: To evaluate the umbilical arterial blood flow velocity and its various indices during 3rd trimester of pregnancy and to compare these indices in normal and growth restricted pregnancies. Methods: In this study, 50 women with normal singleton pregnancy and 50 women with intrauterine growth restricted (IUGR) pregnancy with expected birth weight <10th percentile of the normal for the gestational age were studied by Doppler evaluation of their umbilical artery, Pulsality Index (PI), Resistance Index (RI) and S/D ratio of the control group and IUGR group were calculated and reference range constructed. Values of Doppler indices of IUGR group were compared with those of the control group. Perinatal outcome was evaluated in relation to the indices. Results: Doppler velocimetry of umbilical artery showed elevated indices in 33 out of 50 cases of IUGR group showing its high sensitivity in diagnosing haemodynamically compromised growth restricted fetuses. Absent end diastolic velocily (AEDV) and reversed end diastolic velocily (REDV), were seen in 8 and 2 cases respectively and were associated with poor perinatal out come in terms of need for LSCS for fetal distress, Apgar score <7 at 1 minute, admission to NICU (Neonatal Intensive Care Unit) and perinatal death. Conclusion: In normal pregnancy there is gestational age related fall in impedance in Umbilical arteries. Doppler study of umbilical artery is highly sensitive in the detection of IUGR and for the prediction of adverse perinatal outcome in small for gestational age. Bangladesh J Obstet Gynaecol, 2020; Vol. 35(2): 68-73